Digital Women’s Literature in the Italian High Schools: Canon and Invisible Feminist Writers in Study Plans - Giulia Gerratana (Asparkía)
The inadequate representation of Italian women writers in the Italian school curriculum has been a topic of concern over the last few years, raising questions about their exclusion from the literary school canon despite their contributions. Through an examination of the relationships between gender, literature, and education, altogether with the feminist critique work carried out since the 1970s, this paper seeks to explore digital learning environments that promote gender-related reflections in Italian secondary schools and to examine key factors that have contributed to the invisibility of Italian women writers in educational contexts. Through the specific quantitative analysis of the digital textbook Letteratura Oggi, tomes 3A and 3B, intended for the students of the Italian lyceum last year, this article addresses the presence of any improvements made for major equity between writers.